2006
DOI: 10.2164/jandrol.05154
|View full text |Cite
|
Sign up to set email alerts
|

Psychobiological Correlates of Delayed Ejaculation in Male Patients With Sexual Dysfunctions

Abstract: The pathogenesis of delayed ejaculation (DE) is rather unknown, though the contribution of various psychological, marital, hormonal, and neurological factors has been advocated. In this study we systematically investigated the relative relevance of the aforementioned factors in 1632 men who were seeking medical help for sexual dysfunction. The severity of DE was classified according to Kaplan criteria. Mild and moderate forms of DE (MMDE) recognized different risk factors than the most severe ones (anejaculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
72
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 31 publications
13
72
1
2
Order By: Relevance
“…Even in general population, remarkably scarce studies investigated this problem. So, Corona et al [42] reported it among 62 of 1632 (3.8%) men while Rowland et al [43] claimed it to be present in 2% among 1400 men.…”
Section: Discussionmentioning
confidence: 99%
“…Even in general population, remarkably scarce studies investigated this problem. So, Corona et al [42] reported it among 62 of 1632 (3.8%) men while Rowland et al [43] claimed it to be present in 2% among 1400 men.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, few data were available about delayed ejaculation (DE) and its relational correlates. The main pathogenic mechanism of DE is probably an uncoupling between genital and subjective arousal (Rowland, 2005), which can be exacerbated by partner's impaired orgasm ability (Corona et al, 2006b), creating a vicious cycle. While some women enjoy the extended intercourse, others may experience pain, question their own attractiveness, or suspect the partner's infidelity (Perelman, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ejaculatory time, coital frequency, and timing should be investigated (Krausz and Forti 2000;Nieschlag et al 2010;Grumbach and Styne 2003). Both thyroidal hormones and testosterone levels have been observed to be associated with ejaculatory dysfunction (Corona et al 2004b(Corona et al , 2006a(Corona et al , 2008Carani et al 2005;Cihan et al 2009). In particular, hyperthyroidism has been associated to premature ejaculation while hypothyroidism has been related to delayed ejaculation (Corona et al 2004b(Corona et al , 2006aCarani et al 2005;Cihan et al 2009).…”
Section: Medical and Reproductive Historymentioning
confidence: 99%
“…Both thyroidal hormones and testosterone levels have been observed to be associated with ejaculatory dysfunction (Corona et al 2004b(Corona et al , 2006a(Corona et al , 2008Carani et al 2005;Cihan et al 2009). In particular, hyperthyroidism has been associated to premature ejaculation while hypothyroidism has been related to delayed ejaculation (Corona et al 2004b(Corona et al , 2006aCarani et al 2005;Cihan et al 2009). In addition, specific treatment of those thyroidal dysfunctions are associated to the reduction of the prevalence of the relative ejaculatory dysfunction Carani et al 2005;Cihan et al 2009).…”
Section: Medical and Reproductive Historymentioning
confidence: 99%
See 1 more Smart Citation